Tracing Colonial Maternalism Within the Gendered Morals of Humanitarianism: Experiences of Migrant Women at the Moroccan-Spanish Border - Sahraoui, Nina; Tyszler, Elsa (Frontiers in Human Dynamics, 2021)
By bringing together two sets of qualitative fieldwork conducted in 2016 and 2017 with humanitarian organizations and migrant women on the two sides of the Eastern Moroccan-Spanish border, this article examines the ways in which women humanitarians exercise power over women’s lives, bodies and mobility. Though humanitarianism in the border context has been researched at European and US-Mexico borders, the specifically gendered implications of humanitarian governance at borders needs further investigation. Drawing on interviews and participant observation with a religious humanitarian organization on the Moroccan side of the border and with medical humanitarians and social workers on the Spanish side, we researched women humanitarians’ interventions towards migrant women from West African, North African and Middle Eastern countries. Beyond the differences that characterize these religious and socio-medical humanitarian settings and the different migration regimes in which they are inscribed, we argue that the power exerted by women humanitarians reproduces a form of maternalism underpinned by gendered moral beliefs regarding women’s bodies, mobility and family life. We foreground that such maternalism represents a cornerstone of women’s humanitarian engagement across time and we identify continuities between colonial maternalism, contemporary forms of humanitarian care carried out by women and maternalist integration politics in Western postcolonial societies. Rooted in colonial maternalism, racialized beliefs justified women’s (religious, medical, social) prominent role in intervening in the intimate spaces of women casted as radically Other. Our contemporary case studies demonstrate how the practices of women humanitarians impact on racialized migrant women’s daily lives, intruding on their intimacy, imposing controls over their bodies and impacting on their possibilities for mobility. The article explores how the racialization of migrant women, articulated with moral ideas around women’s reproductive health and mothering responsibilities, produce varied forms of disciplining and control on both sides of the border Moroccan-Spanish border.